Effect of Cement on Strength Properties of Recycled Construction and Demolition Materials - Riyad, ASM; Asha, Md Zakir Hasan (Journal of Engineering Science, 2020)
Evaluation of innovative ways is necessary to use a huge amount of recycled construction and demolition materials generated in Bangladesh and require satisfaction considering environmental, economic and engineering perspectives. In that sense, this study evaluates the outcomes when stabilized with locally available ordinary Portland cement. Furthermore, this study evaluates the research laboratory characterization of physical, geotechnical, and strength properties of unbound construction and demolition materials, for example, reclaimed asphalt from the pavement (RAP), recycled crushed concrete (RCA) and crushed brick (CB). The results advocated that cement can be a feasible alternative for the stabilization of unbound construction and demolition materials. Based on the test outcomes, RAP, CB, and RCA were found to require 2% of cement to meet the requirements for stabilization with a curing duration of 7 days. Journal of Engineering Science 11(1), 2020, 09-17